Hubungan Peran Tenaga Kesehatan Dengan Penggunaan Alat Kontrasepsi Bawah Kulit (AKBK) Di Puskesmas Labuhan Deli Kecamatan Labuhan Deli Kabupaten Deli Serdang Kecamatan Labuhan Deli Kabupaten Deli Serdang Tahun 2023 - Sonia Novita Sari; Sulastri Sulastri; Marlina Lasmawati Simbolon; Imarina Tarigan (Jurnal Anestesi, 2024)
Family Planning (KB) is an action in helping married couples avoid unwanted births, get the desired birth, and regulate birth intervals. The purpose of this study is to relationship the role of health workers with the use of under-skin contraceptives (AKBK) at the Labuhan Deli Health Center, Labuhan Deli District, Deli Serdang Regency in 2023. The method was carried out using analytical observational research with a cross-sectional study design with a population of 45 acceptors. By collecting data using a closed questionnaire that is self-administered questionare. The results of statistical analysis using the chi square test stated that there was a relationship between the role of health workers and the use of AKBK in Puskesmas at the Puskesmas Labuhan Deli, Labuhan Deli District, Deli Serdang Regency with a p-value of 0.006 (p-value < 0.05)